The Relationship Between Strength and Endurance Training on Muscle Fiber Adaptation: A Systematic Review - Charmila Tandi Rerung (Universitas Pejuang Republik Indonesia, 2026)
Background: Muscle fiber adaptation is a central mechanism through which the human body responds to systematic physical training. Understanding the relationship between strength training and endurance training in shaping muscle fiber phenotype is critical for optimizing sports performance, health, and rehabilitation outcomes. Objectives: This narrative review examines the relationship between strength training and endurance training with respect to skeletal muscle fiber adaptations, including morphological, metabolic, and molecular changes in Type I and Type II fibers. Methods: A literature search was conducted using Google Scholar, PubMed, and Scopus (2015–2025) using relevant keywords. Studies involving human subjects with a minimum 4-week training intervention and fiber-type assessment via biopsy or myosin heavy chain (MHC) isoform analysis were included. Results: Strength training predominantly induces Type II fiber hypertrophy through mTORC1/IGF-1 signaling, increases cross-sectional area (CSA) of fast-twitch fibers, and preserves neuromuscular innervation of Type II fibers across the lifespan. Endurance training promotes Type I fiber dominance through PGC-1α/AMPK activation, mitochondrial biogenesis, and enhanced oxidative capacity. Concurrent training produces a mixed adaptive profile dominated by Type IIa hybrid fibers, with evidence of a small negative interference effect on Type I fiber hypertrophy. Aging-related Type II fiber atrophy is most effectively attenuated by chronic strength training. Conclusions: Strength and endurance training produce distinct but complementary adaptations in muscle fiber phenotype. Integrating periodized concurrent training can maximize overall fiber plasticity for diverse performance and health goals.